A Preliminary Evaluation of The Karst Flora of Brazil Using Collections Data - Bystriakova, Nadia; Alves De Melo, Pablo Hendrigo [UNESP]; Moat, Justin; Lughadha, Eimear Nic; Monro, Alexandre K. (Springer Nature, 2019)
Karst is defined as landscapes that are underlain by soluble rock in which there is appreciable water movement arising from a combination of high rock solubility and well-developed secondary (fracture) porosity. Karsts occupy approximately 20% of the planet’s dry ice-free land and are of great socioeconomic importance, as they supply water to up to 25% of the world’s population and represent landscapes of cultural and touristic importance. In Southeast Asia karst is associated with high species-richness and endemism in plants and seen as priority areas for the conservation of biodiversity. There has been little research into the floras associated with karst in South America, most of which occurs in Brazil. We therefore sought to evaluate the importance of Brazilian karst with respect to its species-richness and endemism. We sought to do so using curated plant specimen data in the Botanical Information and Ecology Network (BIEN) dataset. We show that, except for Amazonia, the BIEN dataset is representative of the Brazilian flora with respect to the total number of species and overall patterns of species richness. We found that karst is under-sampled, as is the case for much of Brazil. We also found that whilst karst represent an important source of plant diversity for Brazil, including populations of approximately 1/3 of the Brazilian flora, it is not significantly more species-rich or richer in small-range and endemic species than surrounding landscapes. Similarly, whilst important for conservation, comprising populations of 26.5–37.4% of all Brazilian species evaluated as of conservation concern by International Union for Nature Conservation (IUCN), karst is no more so than the surrounding areas. Whilst experimental error, including map resolution and the precision and accuracy of point data may have under-estimated the species-richness of Brazilian karst, it likely represents an important biodiversity resource for Brazil and one that can play a valuable role in conservation. Our findings are in sharp contrast to those for Southeast Asia where karst represents a more important source of species-richness and endemism. We also show that although BIEN represents a comprehensive and curated source of point data, discrepancies in the application of names compared to current more comprehensive taxonomic backbones, can have profound impacts on estimates of species-richness, distribution ranges and estimates of endemism.